PENGARUH PROFESIONALISME DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT DENGAN TIME BUDGET PRESSURE SEBAGAI MODERASI - Iqbal Najmudin Sholeh (2023)
By releasing audited financial statements, audited financial statements are relied upon by decision makers because report users know that the reports are accurate, and free from material misstatements. If the financial statements are audited, investors will have more confidence because the auditor has verified their accuracy. This research aims to see whether there is an effect of professionalism and auditor independence on audit quality with time budget pressure as a moderating variable. This study uses a quantitative method with the sample being auditors who are in public accounting firms located in the south Jakarta area. The data collection technique used simple random sampling with a sample size of 110 respondents. The data was processed and tested using the Partial Least Square method with the SmartPLS.3.0 application. The results of this study indicate that auditor professionalism has a significant positive effect on audit quality and auditor independence has a significant positive effect on audit quality. Meanwhile, time budget pressure cannot strengthen the relationship between auditor professionalism on audit quality and time budget pressure cannot strengthen the relationship between auditor independence on audit quality.